Biochemistry and molecular biology compendium - Lundblad, Roger L. (Boca Raton : CRC Press, 2019)
"This book is an accessible resource offering practical information not found in more database-oriented resources. The first chapter lists acronyms with definitions, and a glossary of terms and subjects used in biochemistry, molecular biology, biotechnology, proteomics, genomics, and systems biology. There follows chapters on chemicals employed in biochemistry and molecular biology, complete with properties and structure drawings. Researchers will find this book to be a valuable tool that will save them time, as well as provide essential links to the roots of their science"--
OCLC-licensed vendor bibliographic record.
Keywords: Biochemistry -- Handbooks, manuals, etc; Molecular biology -- Handbooks, manuals, etc; MEDICAL / Biochemistry; SCIENCE / Life Sciences / Biology / Molecular Biology; MEDICAL / Biotechnology